2012
DOI: 10.1371/journal.pntd.0001518
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse and Dynamic Nature of Leishmania Parasitophorous Vacuoles Studied by Multidimensional Imaging

Abstract: An important area in the cell biology of intracellular parasitism is the customization of parasitophorous vacuoles (PVs) by prokaryotic or eukaryotic intracellular microorganisms. We were curious to compare PV biogenesis in primary mouse bone marrow-derived macrophages exposed to carefully prepared amastigotes of either Leishmania major or L. amazonensis. While tight-fitting PVs are housing one or two L. major amastigotes, giant PVs are housing many L. amazonensis amastigotes. In this study, using multidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 42 publications
5
89
0
6
Order By: Relevance
“…4; also see Movie S4). Rab7 is a marker of late endosomes and phagolysosomes, which can be observed in the membrane of PVs formed by L. amazonensis or T. cruzi in the first few hours postinfection in vitro (47,73). At the beginning of our recordings, MT forms could be seen surrounded by Rab7; a flagellum also could be inferred from Rab7 contours (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…4; also see Movie S4). Rab7 is a marker of late endosomes and phagolysosomes, which can be observed in the membrane of PVs formed by L. amazonensis or T. cruzi in the first few hours postinfection in vitro (47,73). At the beginning of our recordings, MT forms could be seen surrounded by Rab7; a flagellum also could be inferred from Rab7 contours (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…T. cruzi resides in a transient parasitophorous vacuole (PV) from which the parasite escapes into the host cell cytosol, where it then multiplies (72). L. amazonensis develops in spacious PVs containing dozens, even hundreds, of multiplying parasites that remain in these vacuoles until their transfer to other host cells (73,74). Due to the morphology of large L. amazonensis PVs, it is possible to study coinfection between L. amazonensis and T. cruzi forms.…”
mentioning
confidence: 99%
“…Once at the site of infection, any drug must first permeate the infected macrophage membrane before crossing the membrane of the PV and finally cross the plasma membrane of the parasite (Figure 1). Studies using live imaging of immunolabeled parasites and lysotracker dyes have shown the dynamic nature of PV [3]. These studies showed that the increase in size of L. amazonensis PVs was associated with a decrease in acidic vesicles within infected macrophages.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…The form and size of the PV varies for different Leishmania species. L. mexicana and L. amazonesis live in large communal PV that contain several parasites within the one membrane whereas PVs of L. donovani and L. major are relatively small and contain fewer amastigotes [3,4]. The parasites maintain an acidic pH in the PV to favor their intracellular survival and they have access to nutrients brought by new endosomes or can take in substances via their posterior pole, which has tight contact future science group Review Shaw & Carter with the PV membrane.…”
mentioning
confidence: 99%
“…Four different microscopic fields of each sample were recorded. Live-cell serial images were processed by Imaris software (Bitplane) as follows on the basis of methods previously established (19). Isosurfaces were constructed on the basis of the calcofluor signal, which allowed the assessment of several morphological parameters, such as volume, area, and relative fluorescence intensity.…”
Section: Figmentioning
confidence: 99%